Implementasi Pembelajaran Tari Situasional dan Dampaknya Terhadap Anak Usia Dini - Hilda Zahra Lubis; Luthfia Rizka Fadhila; Sarah Rizky Aulia; Septia Putri Anggraini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the implementation of dance learning and its impact on motor skill development in early childhood at RA Al-Ikhlasiyah 2 Medan. The research is grounded in the understanding that dance activities contribute significantly to children's gross and fine motor coordination, emotional expression, and self-confidence. The study employed a qualitative descriptive approach through observations, interviews with teachers, and documentation of dance sessions. Findings revealed that dance learning was not conducted regularly, but rather situationally ahead of graduation events, with limited integration into daily curriculum. The instructional method mainly involved direct demonstration and repetitive practice, which limited children's opportunities for exploration and creative expression. However, most children responded positively, showing enthusiasm and progress in movement coordination and group participation. Teachers played a key role in motivating children, although time constraints and lack of curriculum support posed challenges. The study concludes that dance learning, when implemented as a structured and routine activity, holds great potential in supporting holistic child development. The research also suggests future efforts to design integrative thematic dance modules and teacher training for sustainable early childhood arts education.